The new Southeast Asian genus Cambonilla gen. nov. (Zodariidae, Araneae): ‘bis repetita placent’ - Jocqué, Rudy; Jocque, Merlijn; Stock, Willem; Rin, Naroeun; Henrard, Arnaud (European Journal of Taxonomy, 2019)
The new genus Cambonilla Jocqué gen. nov. is described on the base of two species, each known from both sexes. A cladistic analysis based on morphology, showed that the new genus is the sister-group of Heliconilla Dankittipakul, Jocqué & Singtripop, 2012 with which it shares the granulated carapace with branched setae and the marbled ventral abdominal pattern, but differs by the abdominal, tubular sclerotized protrusion around the pedicel in males and the absence of posterior ventral abdominal spines in the female. The type species Cambonilla securicula Jocqué gen. et sp. nov. was found in rainforest along the Mekong River in Cambodia and Laos. The second species Cambonilla symphonia Jocqué & Henrard gen. et sp. nov., provided with conspicuous femoral stridulating organs, was recorded from the same localities but in Cambodia only. An illustrated key to the genera of tropical Asia is presented.